The Implementation of Programming Coding-Assisted Problem Based Learning Media to Improve Students’ Mathematics Learning Outcomes - Kris Priyanto; Harry Dwi Putra ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematics learning at the junior high school level aften encounters difficulties, particularly in students’ understanding of plane geometry concepts. These difficulties are largely caused by abstract instructional approaches and the limited integration of technology that can support students’  conceptual visualization and problem-solving processes. This study aims to improve students’ mathematics learning outcomes on plane shapes through the implementation of a programming coding-assisted Problem Based Learning (PBL) model. This research employed a quansi-experimental method using a pretest-posttest control group design. The participants consisted of 32 seventh-grade students at SMP Dewi Sartika Bandung, selected through purposive sampling. The experimental group received instruction using the PBL model supported by C++ programming, while the control group was taught using conventional learning methods. Data were collected using learning achievement test, observation sheets, and documentation of learning activities. The data were analyzed using descriptive statistics, normalized gain analysis, and an independent samples t-test to determine the effectiveness of the learning model. The results showed a significant improvement in students’ mathematics learning outcomes in the experimental group. The average pretest score increased from 55 to 82 in the posttest, with a normalized gain score in the medium-high category. In addition, students in the experimental group demonstrated higher learning activity motivation, and problem-solving skills compared to those in the control group. It can be concluded that programming coding-assisted Problem Based Learning is effective in improving students’ understanding of plane geometry concepts and enhacing their mathematics learning outcomes. This learning approach also supports active learning and the development of 21 st-century skills.